PERLINDUNGAN HUKUM TERHADAP ANAK DIBAWAH UMUR YANG BERHADAPAN DENGAN HUKUM DALAM PROSES DIVERSI - Sukarno, Sukarno; Sumarni, Sumarni (Nusantara Hasana Berdikari, 2022)
This research is entitled legal protection for minors who are in conflict with the law in the diversion process. The research method used is normative research, namely research that examines and analyzes laws and regulations, legal principles and legal norms that are applied as rules or norms which are standards for proper human behavior. The results of the study indicate that the protection of children in conflict with the law in its settlement involves all parties including the role of parents, family, community, government, other state institutions that are obliged and responsible for improving the welfare of the child, as well as special protection for the child concerned. By paying attention to resolving conflicts that occur by using a restorative justice approach that prioritizes restoration of the situation rather than retaliation in resolving cases of children in conflict with the law and prioritizing the best interests of children for their welfare. Diversion is the best form of penal mediation to overcome the problem of child offenders, because it pays more attention to human rights issues with a restorative justice approach. Diversion is not applied to all criminal acts committed by children. This is expressly regulated in Article 7 paragraph (2) of the SPPA Law which states that Diversion is carried out in the event that the crime committed is punishable by imprisonment for under 7 (years); is not a repetition of a crime. In the SPPA Law, it is mandatory for diversion to be carried out at the investigation level as regulated in the provisions of Article 7, Article 27, Article 28, and Article 29 of the SPPA Law. If detailed, Diversion is carried out at the investigation level, usually in practice Diversion can also be carried out at the examination level at the Children's trial Diversion can also be carried out at the prosecution level then the results of the Diversion agreement can be in the form of, Peace with or without compensation, Handing back to parents/guardians, Participation in investigation or training in educational institutions or training in educational institutions or LPKS for a maximum of 3 (three) months; or community service. Â